(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
Comments on the paper “The Geological record of the oldest historical tsunamis in southwestern Spain” by Francisco Ruiz, Manuel Abad, Joaquín Rodríguez Vidal, Luis Miguel Cáceres, María Luz González-Regalado, María Isabel Carretero, Manuel Pozo & Francisco Gómez Toscano.